1983
DOI: 10.1111/j.1471-0528.1983.tb08621.x
|View full text |Cite
|
Sign up to set email alerts
|

An ultrastructural study of menstrual blood in normal menstruation and dysfunctional uterine bleeding

Abstract: Summary. Menstrual fluid was obtained from the uterine cavity and vagina in 20 women within the first 48 h of menstruation. Ten of the women had normal menstrual cycles and blood loss and ten were patients with dysfunctional uterine bleeding. The menstrual samples were examined by electron microscopy for the presence of fibrin and platelets and nearly all were found to contain both fibrin and aggregating platelets. By a simple quantitative system no differences in fibrin and platelet content were found betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…In skin wounds large amounts of fibrin are deposited both inside and outside torn blood vessels (Webster et al 1979), but fibrin fibres are observed inside the blood vessels of the endometrium only during menstruation (Sixma et al 1980). Menstrual fluid contains fibrin and fibrin degradation products but no fibrinogen (Sheppard et al 1983). Women with dysfunctional uterine bleeding (DUB) have increased fibrinolytic activity in their menses compared to controls, but peripheral fibrinolytic activity is unaltered (Bonnar et al 1982).…”
Section: Discussionmentioning
confidence: 99%
“…In skin wounds large amounts of fibrin are deposited both inside and outside torn blood vessels (Webster et al 1979), but fibrin fibres are observed inside the blood vessels of the endometrium only during menstruation (Sixma et al 1980). Menstrual fluid contains fibrin and fibrin degradation products but no fibrinogen (Sheppard et al 1983). Women with dysfunctional uterine bleeding (DUB) have increased fibrinolytic activity in their menses compared to controls, but peripheral fibrinolytic activity is unaltered (Bonnar et al 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings that they are unable to aggregate and metabolize arachidonic acid via the cyclo-oxygenase pathway support this suggestion, but since we collected menstrual fluid from the vagina rather than from the uterine cavity, lack of platelet activity could be due to some effect from cervical or vaginal secretions. On the other hand, ultrastructural studies of platelets collected from both the uterine cavity and the vagina show that they are largely devoid of dense granules (Christiaens et al 1981;Sheppard et al 1983). Furthermore since degranulated platelets have also been observed in endometrial haemostatic plugs, platelets found in menstrual fluid inside the uterus have probably been involved in a coagulation process there (Christiaens et al 1980).…”
Section: Discussionmentioning
confidence: 99%
“…In ovulatory DUB, endometrial histology can vary from proliferative and secretory to menstrual-type. The causes of ovulatory DUB have not been well defined, but some theories suggest a loss or change in endometrial hemostasis, [13][14][15] and alterations in the synthesis and release of prostaglandins are key etiological factors. [16][17][18] Uterine vascular …”
Section: Dysfunctional Uterine Bleedingmentioning
confidence: 98%